2015
DOI: 10.1039/c5ra08067c
|View full text |Cite
|
Sign up to set email alerts
|

Dispersity control of linear poly(glycidyl ether)s by slow monomer addition

Abstract: In this communication we demonstrate that the extent of dispersity of poly(allyl glycidyl ether) and poly(ethoxy ethyl glycidyl ether) can be reduced using a slow monomer addition technique with potassium tert-butoxide as initiator and THF as solvent at 45 C. Different feed rates were examined in triplicate and analysed by SEC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Step-Wise Monomer Addition A recent literature by Groll and coworkers demonstrated that the dispersity of poly(glycidyl ether)s was controlled by slow monomer addition. 35 Therefore, we followed a similar approach, and the monomer was added stepwise (one addition of 25 μL monomer every hour) into the solution containing C(A-P)/ t-BuP 4 /i-Bu 3 Al in MeTHF at both 0 and −20 C (P2-8 and P2-9, respectively, Table 2). However, we have not seen an improvement in the case of stepwise monomer addition.…”
Section: Effect Of Temperaturementioning
confidence: 99%
“…Step-Wise Monomer Addition A recent literature by Groll and coworkers demonstrated that the dispersity of poly(glycidyl ether)s was controlled by slow monomer addition. 35 Therefore, we followed a similar approach, and the monomer was added stepwise (one addition of 25 μL monomer every hour) into the solution containing C(A-P)/ t-BuP 4 /i-Bu 3 Al in MeTHF at both 0 and −20 C (P2-8 and P2-9, respectively, Table 2). However, we have not seen an improvement in the case of stepwise monomer addition.…”
Section: Effect Of Temperaturementioning
confidence: 99%
“…In order to limit the degree of SM, we designed novel polyethers with additional steric hindrance around the pendent olefin. Using potassium tert -butoxide as initiator, which is easier to handle than potassium benzoxide, p­(AGE), poly­(crotyl glydidyl ether) p­(CGE), poly­(prenyl glydidyl ether) p­(PGE) and poly­(methallyl glydidyl ether) p­(MAGE) were synthesized in high molar masses and low dispersity (Figure ) from the corresponding epoxide monomers . It is worth noting that the grafted polymer units resulting from CM with p­(AGE), p­(CGE) and p­(PGE) will be the same, while CM with p­(MAGE) will lead to a trisubstituted olefin.…”
mentioning
confidence: 99%
“…Moeller's works 35 have demonstrated this phenomenon, as shown in However, the use of potassium counterion and keeping the reaction at temperatures below 60 C makes it possible to achieve EEGE polymers with a molar mass of about 30 kg/mol without significant amounts of vinyl end groups. 35 Later studies showed 36 Polymerization and copolymerization of other glycidol derivatives than EEGE were carried out by Moeller's group. 37 The use of tertbutyl and allyl glycidyl ether in addition to EEGE in the copolymerization and then the selective hydrolysis of acetal groups in EEGE units lead to well-defined copolymers containing reactive hydroxyl and allyl groups.…”
Section: Anionic Polymerization Of Glycidol With Protected Hydroxyl G...mentioning
confidence: 99%